Detection of Interleukin-2 and Interleukin-31 among Patients with Uremic Pruritus - Hiba Mohammed Jasim; Ismail Ibrahim Latif; Nabeel Khalid Al Wandi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Uremic pruritus is a form of chronic itching that affects patients with advanced end-stage renal disease. Itis one of the most common symptoms in patients with end-stage renal disease, with approximately 60–90percent of patients on hemodialysis (HD) experiencing it. The study aims to assess the role of interleukin-31and Interleukin-2 in the pathogenesis of uremic pruritus among hemodialysis patients attending the EbnSina Dialysis Center in Diyala, and Correlation between Interleukin 31 and Interleukin-2 with severityof uremic pruritus. A study was performed from 1 Sep 2020 to 20 Jan 2021 in Ebn Sina Dialysis center,Diyala Governorate. the study was conducted on 150 patients with CKD divided to two groups, 75 patientswith uremic pruritus and 75 patients without uremic pruritus, the control groups was 26 healthy persons.Itch intensity was scored by VAS as mild, moderate and severe. Serum IL-31 levels and serum IL-2 levelswere determined by the enzyme-linked immunosorbent assay methodology. The various characteristics pfpruritus was assessed using an interview questionnaire. MS excel package and SPSS 20 software was usedfor analysis. Among 226 HD patient excluded under 20 age and hepatitis C and Hepatitis B HD patients,33.8% had uremic pruritus. The patients with pruritus had higher serum IL-31 levels and IL-2 than thosewithout uremic pruritus and control groups, it was statically significant. As well as the IL-31 and IL-2showed no significant differences among patients with mild, moderate, and severe itch. IL-31 and IL-2 playimportant role in the pathogenesis of uremic pruritus. Further studies to confirm the role of cytokines in thepathogenesis of UP.